Enabling the high capacity of lithium-rich anti-fluorite lithium iron oxide by simultaneous anionic and cationic redox. Issue 12 (December 2017) - Zhan, Chun; Yao, Zhenpeng; Lu, Jun; Ma, Lu; Maroni, Victor; Li, Liang; Lee, Eungje; Alp, Esen; Wu, Tianpin; Wen, Jianguo; Ren, Yang; Johnson, Christopher; et al.
Abstract Anionic redox reactions in cathodes of lithium-ion batteries are allowing opportunities to double or even triple the energy density. However, it is still challenging to develop a cathode, especially with Earth-abundant elements, that enables anionic redox activity for real-world applications, primarily due to limited strategies to intercept the oxygenates from further irreversible oxidation to O2 gas. Here we report simultaneous iron and oxygen redox activity in a Li-rich anti-fluorite Li5 FeO4 electrode. During the removal of the first two Li ions, the oxidation potential of O2− is lowered to approximately 3.5 V versus Li+ /Li0, at which potential the cationic oxidation occurs concurrently. These anionic and cationic redox reactions show high reversibility without any obvious O2 gas release. Moreover, this study provides an insightful guide to designing high-capacity cathodes with reversible oxygen redox activity by simply introducing oxygen ions that are exclusively coordinated by Li+ . It is challenging to exploit anionic redox activity to boost performance of battery electrodes, especially for anti-fluorite structures. Here the authors report simultaneous anionic and cationic redox in Li5 FeO4, which enables its high capacity and eliminates the undesired oxygen gas release.